Incorporating Watermelon Rind into Jackfruit Seed Drink: A Functional Drink Rich in Antioxidant and Phenolic Compounds - William Ben Gunawan; Lauw Eunike Azalia Septianawati Basoeki (EDUFORTECH, 2022)
Functional foods have been widely consumed as a treatment for managing diabetes because of their nutrition composition, phenolic, and other phytochemical compounds. Higher antioxidant activity, vitamin C, and total phenolic content may be linked with a higher antidiabetic property of a food product. Jackfruit seed and watermelon rind – albeit their various health benefits – are often discarded as food waste. Moreover, watermelon rind consists of citrulline which was known to regulate blood glucose levels. This research aims to determine antioxidant activity, vitamin C, and total phenolic content in jackfruit seed drink (JSD) enriched with watermelon rind as a functional drink with antioxidant and antidiabetic properties. Three formulations of JSD (JSD0, JSD1, and JSD2) were created based on the variation of watermelon rind composition. Vitamin C content was determined using iodometric titration while the phenolic content was measured using the Folin-Ciocalteu method. Antioxidant activity was observed based on the inhibition of DPPH. The results showed a significant difference between formulas based on vitamin C, total phenolic content, and antioxidant activity (p0.05) with JSD 2 as the best formula. JSD 2 showed vitamin C, total phenolic, and antioxidant activity of 37.83 ± 0.68 mg/100g; 29.86±0.60 mgGAE/g; 40.98±0.78%. Incorporating watermelon rind into JSD significantly increased the nutrition values, antioxidant activity, and the potential health benefits of JSD.